Uncovered interest parity in a partially Dollarized developing country: Does UIP hold in Bolivia (and if not, why not?) - Ola Melander (Stockholm School of Economics, The Economic Research Institute (EFI), 2009)
According to the Uncovered Interest Parity (UIP) condition, interest rate differentials compensate for expected exchange rate changes, equalizing the expected returns from holding assets which only differ in terms of currency denomination. In the previous literature, there are many tests of UIP for industrialized countries, and, more recently, some tests for emerging economies. However, due to data availability problems, poorer developing countries have not been studied. This paper tests UIP in a partially dollarized economy, Bolivia, where bank accounts only differ in terms of currency denomination (U.S. dollars or bolivianos). I find that UIP does not hold in Bolivia, but that the deviations are smaller than in most other studies of developed and emerging economies. Moreover, several factors seem to contribute to the deviations from UIP. The so-called peso problem could possibly account for the observed data, but there is also evidence of a time-varying risk premium, as well as deviations from rational expectations.
Keywords: E43; F31; G15; 330; Uncovered interest parity; UIP; partial dollarization; time-varying risk premium; peso problem; rational expectations; Zinsparität; Zinsstruktur; Währungssubstitution; Risikoprämie; Rationale Erwartung; Bolivien